Audit-Consulting of Environmental Activity of Oil and Gas Organizations: Organizational-Methodical Aspect - Ruslan Rifovich Rastamkhanov (Учёт. Анализ. Аудит, 2019)
Of auditing materials of the theoretical analysis, the methods of comparison were used, as well as the system and process approaches. As an information base there were used the financial reporting and the reporting in the field of sustainable development of Russian oil and gas organizations, which reflects the main results of the activities, including environmental and nature protection activity. Results. The results of the research are the systematization of the indicators that are required for use in the management of environmental activities of the oil and gas organization and are proposed for the inclusion in environmental performance reporting and the developed business-process audit-consulting model that meets modern management requirements. Discussion. The model is universal and can serve as the basis for the development of audit-consulting environmental activities of organizations of different sectoral focus to improve the effectiveness of management decisions based on the information received in the audit-consulting process.